2021
DOI: 10.5432/jjpehss.20123
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stroke frequency and hand propulsive force in the front crawl

Abstract: This study aims at clarifying the factors responsible for the change in hand propulsive force when the stroke frequency was changed. Eight male swimmers performed five 20m-front crawls. The first trial involved maximal effort, whereas the stroke frequency was controlled during the next four trials. The instructed stroke frequencies were 70%, 80%, 90%, and 100% of the stroke frequency at the maximal effort trial. To calculate the hand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Figure 4(e) shows that both F hand and its propelling directional component T hand increased from 70% to 90% SF, peaked at 100% SF, and then decreased from 110% to 120% SF. The increase in the mean T hand was indirectly supported by Schnitzler et al (2011) who showed the propulsive impulse during one stroke cycle was unchanged among five velocity conditions (ranging from 60% to 100% of maximum velocity) with a similar method as Koga et al (2020Koga et al ( , 2021. Given that the stroke duration becomes shorter when increasing SF (34.8 − 51.8 Hz in the study by Schnitzler et al), the mean T hand should also have been increased in their study.…”
Section: Changes In Fluid Mechanic Parameters (Pressure Values F Hand and T Hand ) In Each Stroke Phase At Varied Sfmentioning
confidence: 76%
See 4 more Smart Citations
“…Figure 4(e) shows that both F hand and its propelling directional component T hand increased from 70% to 90% SF, peaked at 100% SF, and then decreased from 110% to 120% SF. The increase in the mean T hand was indirectly supported by Schnitzler et al (2011) who showed the propulsive impulse during one stroke cycle was unchanged among five velocity conditions (ranging from 60% to 100% of maximum velocity) with a similar method as Koga et al (2020Koga et al ( , 2021. Given that the stroke duration becomes shorter when increasing SF (34.8 − 51.8 Hz in the study by Schnitzler et al), the mean T hand should also have been increased in their study.…”
Section: Changes In Fluid Mechanic Parameters (Pressure Values F Hand and T Hand ) In Each Stroke Phase At Varied Sfmentioning
confidence: 76%
“…However, in combination with 3D underwater motion analysis, the direction of the fluid force acting on the hand can also be obtained. Here we present the results of experiments (Koga et al, 2020(Koga et al, , 2021 that measured the kinematic parameters of swimming motion and fluid mechanical parameters acting on the hand for a range of SF. In the following sub-sections, the impact of changing SF on other variables is discussed.…”
Section: Measurement Of Biomechanical and Fluid Mechanic Parameters Using Actual Swimmersmentioning
confidence: 99%
See 3 more Smart Citations